Tratamiento de la peritonitis infecciosa felina con la molécula gs 441524- un reporte de caso (2023)
The internship performed at the veterinary clinic Cat Medical Care, was a source to enter the world of knowledge of cat medicine, in order to enrich in a practical way the theoretical knowledge acquired through the undergraduate studies.